Complementary and alternative treatment in functional dyspepsia. Issue 1 (1st February 2018) - Chiarioni, Giuseppe; Pesce, Marcella; Fantin, Alberto; Sarnelli, Giovanni
Abstract : Introduction and aim: The popularity of complementary and alternative medicine (CAM) in treating functional gastrointestinal disorders (FGIDs) has steadily increased in Western countries. We aimed at analyzing available data on CAM effectiveness in functional dyspepsia (FD) patients. Methods: A bibliographical search was performed in PubMed using the following keywords: "complementary/alternative medicine, " "hypnosis, " "acupuncture" and/or "functional dyspepsia." Results: In community settings, almost 50% of patients with FGIDs used CAM therapies. Herbal remedies consist of multi‐component preparations, whose mechanisms of action have not been systematically clarified. Few studies analyzed the effectiveness of acupuncture in Western countries, yielding conflicting results and possibly reflecting a population bias of this treatment. Hypnosis has been extensively used in irritable bowel syndrome, but few data support its role in treating FD. Conclusions: Although some supporting well‐designed studies have been recently performed, additional randomized, controlled trials are needed before stating any recommendation on CAM effectiveness in treating FD.